1991
DOI: 10.1007/bf01963934
|View full text |Cite
|
Sign up to set email alerts
|

Non-typhoidSalmonella bacteraemia in Greater Copenhagen 1984 to 1988

Abstract: A retrospective survey of non-typhoid Salmonella bacteraemia in the period 1984 to 1988 was carried out by the five departments of clinical microbiology in Greater Copenhagen. A total of 168 patients were identified. A gradual increase was observed from 11 cases in 1984 to 58 cases in 1988. The corresponding incidence per 100,000 inhabitants in Copenhagen rose from 0.9 in 1984 to 5.0 in 1988. During the same period the total registered incidence of human Salmonella infections in Denmark increased from 17.6 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…The relative proportion of Salmonella serogroups and serotypes isolated at a single geographic area or hospital is very variable (5,16,27). Our study, as well as other studies, proves that different serogroups have different patterns of resistance, with serogroups B4,5 and C7 usually being more resistant than serogroup Dg (6).…”
Section: Salmonella Infections Constitute An Important Problemsupporting
confidence: 63%
“…The relative proportion of Salmonella serogroups and serotypes isolated at a single geographic area or hospital is very variable (5,16,27). Our study, as well as other studies, proves that different serogroups have different patterns of resistance, with serogroups B4,5 and C7 usually being more resistant than serogroup Dg (6).…”
Section: Salmonella Infections Constitute An Important Problemsupporting
confidence: 63%
“…However, even among patients 5-60 years old without a known risk factor, ∼25% were admitted to the hospital, mainly because of moderate dehydration. Bacteremia was seen in as many as 12% of the patients admitted to the hospital and disposed patients to other extraintestinal complications [13][14][15]. Beside extraintestinal complications, intestinal complications and unnecessary surgical procedures to treat suspected acute abdominal conditions (appendectomies and laparoscopies without pathologic findings other than mesenteric lymphadenitis) also contributed to morbidity and mortality.…”
Section: Methodsmentioning
confidence: 94%
“…1988; Fischl et al 1986; Glaser et al 1985; Lester et al 1991; Levine et al 1991;Nadelman 1985;Pithie et al 1993) have reported an increasing incidence of non-typhoidal Salmonella bacteraemia, especially in patients infected with human immunodeficiency virus (HIV). In Thailand, the annual reports from the W H O Salmonella and Shigella Center, Department of Medical Science, Ministry of Public Health reveal by a passive surveillance system that the average number of human isolates of Salmonella was 2500 p a .…”
mentioning
confidence: 99%